PENGARUH AGEN GASIFIKASI BATUBARA TERHADAP PRODUK GAS YANG DIHASILKAN OLEH BATUBARA PERINGKAT RENDAH - Agus Triantoro; Adip Mustofa; Riswan Riswan (Universitas Lambung Mangkurat, 2013)
The development of coal gasification has several disadvantages including high reaction temperature and big energy consumption, difficult purification of the gaseous products, and stringent requirements of the process equipment. It has also been pointed out to cause serious environmental pollution. In this study, the experiment was conducted by flowing nitrogen, oxygen, and , into the gasification equipment. The gasification reactor was heated to 600 oC, 700 oC and 800 oC, where dry coal had been initially fed into before the gasification process began. The flow rates of pyrolysis products were then measured and a sample was taken for further analysis by using a gas chromatograph. The analysis identified the products composition that was CO, CO2, H2, CH4, C2H4 and C2H6. The composition of synthesis gas was observed to depend on the gasification agent used. it can be summarized that there is a good correlation between gasification agent and coal used, with the quality and quantity of synthesis gas produced.